Dermatitis caused by the tropical fowl mite Ornithonyssus bursa (Berlese) (Acari: Macronyssidae) : a case report in humans - Mentz, Marcia Bohrer (2015)
We herein report human dermatitis caused by the tropical fowl mite Ornithonyssus bursa (Berlese). The cases occurred in an apartment in a residential district of Porto Alegre City, State of Rio Grande do Sul, Brazil, where three members of the same family presented with pruritic lesions on the arms and legs. On inspecting the bathroom, several mites measuring approximately 1.0mm in length were observed coming from a nest of Rufous Hornero, Furnarius rufus (Gmelin). This is the fi rst report of O. bursa in the urban area of Porto Alegre City, from a nest of F. rufus that bites humans.